IDENTIFICATION OF Z-GEN STUDENT MOTIVATION IN THE INVOLVEMENT WITHIN STUDENT ACTIVITIES IN CAMPUS – A CASE STUDY - Kumendong, Angelica; Panjaitan, Andry; Laurence (AGUSPATI Research Institute, 2021)
To date, University is facing a challenge on how to encourage active participation from its students who come from the Z generation to join student activities. The initial stage that can be done is to identify student motivation in participating in student activities. Motivation is an important method for managing human behavior. This study uses Self-determination theory. This research aims to identify and analyze student motivation that has characteristics of Z generation in the involvement within student activities in the campus, along with the difference in motivation between the student as a participant and as the committee. This research takes the study of Universitas Pelita Harapan Lippo Village, particularly in the Student Life Department which supervises most of the student activities on the campus. The Data collection method uses a questionnaire, and the data processing method uses statistical software. The results of the study show 7 things that encourage students to participate in student activities. From five types of motivation, that is intrinsic motivation, identification type of extrinsic motivation, introjection type of extrinsic motivation, external regulation type of extrinsic motivation, and amotivation, a significant difference between student participant motivation and student committee motivation lies in the introjection type of extrinsic motivation.